THE PEDAGOGICAL IMAGINARY IN ATACAMA DESERT NITRATE MINE SCHOOLS - González, José Antonio (Revista de Historia Social y de las Mentalidades, 2025)
This paper analyzes the school system operation during the nitrate mine cycle in the  Atacama Des ert, pointing out schools, libraries, teachers, students and relations between  primary school teachers and nitrate companies.
Keywords: Schools; Nitrate mines; Atacama Desert; Antofagasta